Perlindungan Hak Anak Hasil Perkawinan Campuran: Analisis Putusan Pengadilan Tinggi DKI Jakarta No.495/PDT/2020/PT DKI Perspektif Maqāṣid al-Syarī‘ah - Al Fikri, Muhammad Mursyid; Iwan, Iwan (AL-SULTHANIYAH, 2025)
This study examines the protection of the rights of children from mixed marriages through the analysis of the Jakarta High Court Decision No. 495/Pdt/2020 using the Maqashid Sharia approach, aiming to understand the application of Sharia principles in determining child custody, especially concerning citizenship and emotional bonds for the child's welfare. The method used is normative juridical with a legislative and case approach, qualitative in nature, focusing on legal reasoning based on principles, doctrines, theories, and applicable legal norms, with data collected through literature studies including primary sources such as the Civil Code, Citizenship Law, Marriage Law, court decisions, secondary materials like books and journals, and tertiary sources such as legal dictionaries and encyclopedias. Descriptive analytical analysis is systematically conducted to describe and analyze the substance of legal protection for children from mixed marriages. The study results show that the application of Maqashid Sharia in the decision emphasizes the importance of protecting citizenship and maintaining the emotional relationship between the child and parents, reflecting a harmonization between positive law and Sharia principles to ensure the best rights and welfare for the child.